Determinan Literasi Kesehatan Ibu Hamil - Yoryanda, Dayang Venty Sukaryuni; Dharmadja, Sobar (Melati Institute, 2025)
The low level of health literacy has a negative impact on health behaviors and health status. This study aims to determine the relationship between health services, health information, and infrastructure with the health literacy of pregnant women. This research is an analytical observational study with a cross-sectional approach, where dependent and independent variables are observed simultaneously. The population consists of 46 pregnant women who visited BPM W.L. Yustini in December 2023 using total sampling technique. Data were processed using computerization and analyzed using univariate and bivariate analysis using the Chi-square test. The results showed that the majority of respondents (71.7%) had poor health literacy, the majority (82.6%) received inadequate health services, some (56.5%) received inadequate health information, and the majority (80.4%) had incomplete facilities and infrastructure. The conclusion of this study is that there is a relationship between health services, health information, infrastructure, and the health literacy of pregnant women (p value= 0.031; p value= 0.011; p value= 0.009).